Assessment of UV-Vis LED-assisted Photo-Fenton Reactor for Atrazine Degradation in Aqueous Solution - Pedro Luis Sanabria Florez; Suellen Aparecida lves; Patricia Los Weinert; Elaine Regina Lopes Tiburtius (Orbital: The Electronic Journal of Chemistry, 2021)
Atrazine is one of the most used pesticides, although it is extremely toxic for living organisms. In spite of that, the control, removal, and elimination of this agrochemical are still deficient in water treatment plants (just over 25%). For this reason, the main objective of this study was to evaluate atrazine degradation efficiency in aqueous solution using the photo-Fenton system assisted by a light-emitting diode (LED) lamp. The degradation results of 30 mg L-1 atrazine evidenced that our approach presented an efficiency of approximately 98% in only 240 minutes of reaction, and the observed mineralization was 60% of total organic carbon (TOC). Several byproducts were identified (such as HA, DEA, DIA, HDEA, HDIA, and HDEDIA), and the degradation mechanism followed dechlorination and hydroxylation pathways that produce HDEDIA or ammelide. In this way, the photo-Fenton system under an LED lamp showed to be highly efficient at removing atrazine from aqueous solutions, offering several advantages compared to the traditional system, such as lower energy consumption and more environmentally friendly features.DOI: http://dx.doi.org/10.17807/orbital.v13i2.1531